The Construction of Independent Character Education from the Perspective of Ibn Qayyim Al-Jawziyyah - Yeny Nasril; Syamsu Nahar; Nurussakinah Daulay (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
The development of the digital age and globalization has posed serious challenges to the character building of the younger generation, particularly in terms of weakening independence, self-regulation, and spiritual resilience. Cognitive-oriented education is considered incapable of responding to the crisis of dependency, instant culture, and the increasing degradation of values. This study aims to reconstruct the concept of independent character education according to the thoughts of Ibn Qayyim al-Jauziyyah and analyze its relevance in the context of contemporary Islamic education. This study uses a qualitative approach with a figure-based study type based on library research. Data were obtained from the primary works of Ibn Qayyim al-Jauziyyah and relevant secondary literature, then analyzed using thematic content analysis techniques. The results show that, according to Ibn Qayyim, independent character education is built holistically through gradual education, exemplary behavior, habituation, simplicity of life, utilization of time, and spiritual control through muhasabah, with tauhid and tazkiyatun nafs as the main foundations. Independence is understood as the freedom of the soul from worldly dependence and lust. The implications of this study emphasize the importance of integrating spiritual values into Islamic character education so that the formation of students' independence is transformative, sustainable, and relevant to the challenges of modern education.